If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2q + -7) + -1(3q + -8) = 22 Reorder the terms: 3(-7 + 2q) + -1(3q + -8) = 22 (-7 * 3 + 2q * 3) + -1(3q + -8) = 22 (-21 + 6q) + -1(3q + -8) = 22 Reorder the terms: -21 + 6q + -1(-8 + 3q) = 22 -21 + 6q + (-8 * -1 + 3q * -1) = 22 -21 + 6q + (8 + -3q) = 22 Reorder the terms: -21 + 8 + 6q + -3q = 22 Combine like terms: -21 + 8 = -13 -13 + 6q + -3q = 22 Combine like terms: 6q + -3q = 3q -13 + 3q = 22 Solving -13 + 3q = 22 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 3q = 22 + 13 Combine like terms: -13 + 13 = 0 0 + 3q = 22 + 13 3q = 22 + 13 Combine like terms: 22 + 13 = 35 3q = 35 Divide each side by '3'. q = 11.66666667 Simplifying q = 11.66666667
| 4x^2-27x+23=-4x+8 | | x+(x+4)=3+(x+1) | | 6x+14=23-3x | | 10x=51-7x | | -14x=7-9x | | x^2-9x-3=-8x-1 | | 3x+4=58-3x | | x^2+4x-28=4 | | 3x+9=79-7x | | -14x=7-9 | | Damn=you | | 10x=90-5x | | 4(3w+5)-30=7w | | 4x+10=40-2x | | x^2+3x-13=2x-1 | | 6x=15+3x | | x^2-2x-4=4 | | 5x+6-1=18+4x-6 | | 64-2x=7x+23 | | 4x+28=13x-81 | | 3x+3x-3+7=3x+11 | | 4x+28=13x-18 | | 10x+26=5x+141 | | A+12+2=5+5+5 | | 12-10x=25-17x | | 2x+18=58-3x | | -45+7X=32 | | 3x+6=26-2x | | 8x=16+-4x | | 8x=16+-4 | | 10x=60-10x | | 4x-12x^2=0 |